Political institutions and health expenditure - Johannes Blum; Florian Dorn; Axel Heuer (International Tax and Public Finance, 2021)
We examine how political institutions influence health expenditure by using a panel of 151 developing and developed countries for the years 2000 to 2015 and four measures of democracy. Our pooled OLS analysis shows that democracies have 20–30% higher government health expenditure relative to GDP than their autocratic counterparts. An instrumental variable approach which exploits the regional diffusion of democracy confirms the positive effect of democracy on government health expenditure. Panel fixed effects and event study models also suggest a positive within-country effect of democratization on government health expenditure within a short period after regime transition. Democratic rule, however, does not turn out to significantly influence private health expenditure compared to autocracies. We conclude that democracies may care more for their citizens and strive to decrease inequalities in the access to health care.
Keywords: I15; I18; H51; P50; C23; C26; 340; Event study; Democracy; Health expenditure; Development; Instrumental variable; Panel data